Public Sector Expenditure to Agriculture, Bank Credits, and Aggregate Output: A Causality Analysis of the Nigerian Evidence - Achumu, James; Ezirim, Ucheoma I.; Ezirim, Chinedu B.; Chekwa, Charles; Hunter, Debra (Journal of Applied Business and Economics, 2022)
This paper investigates the existence or otherwise of causal relationships between direct budgetary government expenditure on agriculture, indirect government funding through credit guarantees, and straight-bank-loans-and-advances to the agricultural sector, on one part, and the gross domestic product of the economy, on the other. It utilized descriptive statistical tools, regression analysis, diagnostic tests, and pairwise Granger causality technique against annual time-series Nigerian data from 1981 through 2019. The results indicates that agricultural credit guaranteed funding and direct credits from such banks like bank of industry and the commercial banks positively and significantly cause, as in affecting and boosting, the country’s GDP. Quite surprisingly, direct government budgetary expenditure on agriculture was revealed to cause and affect GDP, but negatively. The recommendations favor encouraging and increasing the indirect guaranteed funding and straight loans and advances by relevant banks in the country.